2012
DOI: 10.1111/j.1462-5822.2012.01809.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of activation‐associated host cell gene expression by the apicomplexan parasiteTheileria annulata

Abstract: SummaryInfection of bovine leucocytes by Theileria annulata results in establishment of transformed, infected cells. Infection of the host cell is known to promote constitutive activation of pro-inflammatory transcription factors that have the potential to be beneficial or detrimental. In this study we have compared the effect of LPS activation on uninfected bovine leucocytes (BL20 cells) and their Theileria-infected counterpart (TBL20). Gene expression profiles representing activated uninfected BL20 relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 80 publications
(126 reference statements)
4
39
2
Order By: Relevance
“…Hence, these are potentially subject to non-systematic variations resulting from growth in vivo, the given strain analysed and parasite isolation procedures. This variation is apparent when comparing the genes enriched in stumpy cells in different analyses with those enriched in stumpy cells in our study, although we found the best agreement (p<0.001, using a Monte Carlo simulation using 1000 iterations [50]) with the study by Jensen and colleagues [17] ( Data File S9 ). The importance of different isolation procedures for different studies is revealed in the SILAC analysis of stumpy forms where PAD2 was seen to be strongly expressed, likely reflective of parasite cold shock or the induction of early differentiation events during isolation procedures [44].…”
Section: Discussionsupporting
confidence: 60%
“…Hence, these are potentially subject to non-systematic variations resulting from growth in vivo, the given strain analysed and parasite isolation procedures. This variation is apparent when comparing the genes enriched in stumpy cells in different analyses with those enriched in stumpy cells in our study, although we found the best agreement (p<0.001, using a Monte Carlo simulation using 1000 iterations [50]) with the study by Jensen and colleagues [17] ( Data File S9 ). The importance of different isolation procedures for different studies is revealed in the SILAC analysis of stumpy forms where PAD2 was seen to be strongly expressed, likely reflective of parasite cold shock or the induction of early differentiation events during isolation procedures [44].…”
Section: Discussionsupporting
confidence: 60%
“…This is facilitated by the fact that, immediately following entry into the leukocyte, the host cell membrane surrounding the invading sporozoite is dissolved, leaving the developing schizont free in the cytoplasm where it can interact with the host cell cytoskeleton and regulatory components of signalling pathways. Analysis of leukocyte gene expression networks provided evidence that the parasite establishes tight control over pathways associated with cellular activation by modulating reception of extrinsic stimuli and by significantly altering the expression outcome of genes targeted by infection-activated transcription factors (Durrani et al, 2012). Furthermore, at each host cell mitosis and cytokinesis, the schizont co-opts the host’s astral and central spindle microtubules, ensuring its equal distribution between the two daughter cells (Hulliger et al, 1964; von Schubert et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is not surprising that some Theileria species have evolved mechanisms to directly modify host signaling pathways similarly to some cancers [34,35]. We propose that each of the hallmarks that Theileria transformation shares with some cancer cells represents an opportunity for insights into host pathogenesis (Box 1) and potentially new therapeutic approaches for parasite infection.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast to both normal somatic cells and many cancer cells, T. parva-transformed lymphocytes require contact with other infected or uninfected cells to proliferate [85]. The expression levels of known regulators of contact inhibition, Merlin or liver kinase B1, are not reportedly regulated by T. annulata during infection [34,35], suggesting that Theileria-infected cells may achieve contact independence via an as-yet undiscovered mechanism.…”
Section: Evasion Of Growth Suppressionmentioning
confidence: 86%
See 1 more Smart Citation